Austrochlamys heardensis (Fleming, 1957) (Bivalvia: Pectinidae) from Central Kerguelen Plateau, Indian Ocean: palaeontology and possible tectonic significance - Quilty, PG; Murray-Wallace, CV; Whitehead, JM (2004)
Austrochlamys heardensis (Fleming) is recorded from a boulder of Late Pliocene (3.62-2.5 Ma) volcaniclastic sandstone dredged 70 km east-north-east of Heard Island, the third record of the species. The collection is much larger than the original described by Fleming and includes left valves which are described for the first time. The species is compared with A. anderssoni (Hennig) from Cockburn Island and 'Chlamys' mawsoni Fletcher from ÃŽles Kerguelen. The source rock accumulated in fully marine, highly current-affected conditions. The collection is dominated by right valves, possibly because left valves are more susceptible to breakage and the effects of current winnowing. The locality may have subsided some 500 m since deposition. It lies immediately north of a straight, north-east - south-west trending lineament which may mark a major tectonic feature with left-lateral displacement of approximately 50 km, and provides a natural boundary within the Central Province of Kerguelen Plateau.